EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) DAN PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN SAINTIFIK PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMAMPUAN AWAL SISWA SMP KELAS VIII SE-KABUPATEN SRAGEN - Supriyatin, Supriyatin; Kusmayadi, Tri Atmojo; Mardiyana, Mardiyana (Jurnal Pembelajaran Matematika, 2015)
Abstract : The aim of the research was to determine the effect of learning models on mathematics achievement viewed from prior competency. The learning models compared were TPS with scientific approach, PBL with scientific approach and direct learning. This was quasi-experimental research with 3x3 factorial design. The population were all students of Junior High School in Sragen. The samples of research were taken by using the stratified cluster random sampling technique and consisted of 297 students. The instruments used were mathematics achievement test and prior competency test. The data analysis technique used unbalanced two ways anova. Based on the data analysis, it can be concluded as follows. (1) The students treated with PBL learning model with scientific approach provided better learning achievement than those treated with TPS and those treated with direct learning model. The students treated with TPS learning model with scientific approach provided equal mathematics learning achievement to those treated with direct learning. (2) The students with high prior competency had better learning achievement than those with medium and those with low prior competencies. The students with medium prior competency had better learning achievement than those with low one. (3) In the TPS learning model with scientific approach and direct learning, the students with high and medium prior competencies had better learning achievement than those with low one. In the PBL learning model with scientific approach, the students with high prior competency had better learning achievement than those with low prior competencies and both of them provided the same learning achievement than those with medium one. (4) The students with high prior competency category had the same learning achievement in TPS type of learning model with scientific approach, PBL learning model with scientific approach and direct learning model. In medium prior competency category, PBL learning model with scientific approach provided better learning achievement than TPS learning model with scientific approach did, and both of them provided the same learning achievement as the direct learning did. Meanwhile in low prior competency category, PBL learning model with scientific approach provided better learning achievement than TPS learning model with scientific approach and direct learning model, and TPS learning model with scientific approach provided the same learning achievement as the direct learning did.Keywords: Mathematics Learning Achievement, TPS, PBL, Scientific Approach, Prior Competency